Acinar cell carcinoma of the uncinate process of the pancreas in a child managed sans Whipple's procedure-a rare case scenario - Tanvi Goel; Sachit Anand; Anjan Kumar Dhua; Aanchal Kakkar; Sandeep Agarwala; Veereshwar Bhatnagar (Wolters Kluwer Medknow Publications, 2022)
Acinar cell carcinoma (ACC) is a rare malignant tumor of the pancreas. A 10-year-old girl presented with a large tumor arising from the pancreatic head. Excision sans Whipple's procedure was performed. Histopathology revealed it as ACC. In the context of this case, this rare tumor is being reported to highlight that such tumors arising from the head of the pancreas can be managed successfully without always resorting to a Whipple's procedure.